Adult learning and lifelong learning and their socio-economic contribution - Lafta, Ahmed Hamdan; Saleh, Jasim Mohammed; Man, Norsida; Abu Samah, Bahaman; Raja Yusof, Raja Nerina; Mohd Nawi, Nolila (International Institute for Science, Technology & Education, 2016)
This paper provides a synthesis learning from in adult learning literature. The paper starts by looking the rationale for adult learning which has its roots on informal learning. It offers in a nutshell some benefit of learning from adult education perspective. The paper provides a substantiation of a wide-ranging perspective of learning that accommodate social aspect of life than a narrowly understood classroom learning for certification. This paper intends to identify the immediate results of learning, offer the understanding of how learning influence on outcomes and offer practical examples from previous research. Last but not the least, the paper concludes by highlighting the wide understanding of learning from an adult education perspective.